Secretome analysis of cardiomyocytes identifies PCSK6 (proprotein convertase subtilisin/kexin type 6) as a novel player in cardiac remodeling after myocardial infarction - Kuhn, Tim Christian; Knobel, Johannes; Burkert-Rettenmaier, Sonja; Li, Xue; Meyer, Sören; Jungmann, Andreas; Sicklinger, Florian; Backs, Johannes; Lasitschka, Felix; Müller, Oliver J.; Katus, Hugo; Krijgsveld, Jeroen; et al. (Circulation, 2020)
Acute occlusion of a coronary artery results in swift tissue necrosis. Bordering areas of the infarcted myocardium can also experience impaired blood supply and reduced oxygen delivery, leading to altered metabolic and mechanical processes. Although transcriptional changes in hypoxic cardiomyocytes are well studied, little is known about the proteins that are actively secreted from these cells.
Gesehen am 04.12.2020